Dementia in Czechia: Prevalence Estimations Until 2050 - Svacinova, Kornélia; Pechholdova, Markéta (European Journal of Mental Health, 2022)
Introduction: The Czechia is facing population aging. The number of people with dementia is increasing. Conflicting conclusions of European studies confirm the difficulties of quantifying the disease.Aims: We aim to estimate the number of people with dementia in Czechia until 2050: a) projecting dementia prevalence using prevalence rates from EURODEM and EuroCoDe studies, b) projecting dementia based on mortality tables of individuals living with dementia. Comparing both approaches to dementia estimation.Methods: We conducted a literature review. The projection is based on socio-demographic and health variables; construction of life tables for people with dementia.Results: According to the results a) projecting the prevalence of dementia; over 300,000 seniors aged 60+ will suffer from dementia by 2050; b) estimating the number of individuals living with dementia: The number of men and women with dementia aged 65+ was estimated at over 120 thousand.Conclusions: Czech society is not prepared for this intense increase in the number of individuals living with dementia. We argue early diagnosis as well as appropriate health and social care are urgent.